Pengaruh Kenaikan Penghasilan Tidak Kena Pajak (PTKP) Dan Jumlah Wajib Pajak Efektif Terhadap Penerimaan PPh Pasal 21 - Nurul Susanti; Andi (JRB-Jurnal Riset Bisnis, 2018)
This research aims to determine the need for non-taxable income rate to be rised including the number of effective tax-payers on income tax as referred to the Article 21 of the Law No 36 of 2008 has the potential to increase. This study is conducted in KPP Pratama Serang using local population as taxpayers which accept Income Tax (PPh) based on Article 21 or using saturated sample or all population paying income tax (PPh) as respondents in KPP Pratama Serang while taking the period 2014-2016. The method used in this research is fieldwork by visiting the city of Serang as the Capital city of Banten Province to conduct a survey on local population as tax-payers including those working people with non-taxable income status. The results of this study reveal that the number of non-taxable income (PTKP) has a significant effect on the income tax revenue based on the article 21. Additionally, there is a negative beta value, which indicates that the higher rate of non-taxable income adds to an increase in the income tax of Article 21. As noted, the number of effective tax-payers significantly influence the income tax revenue of article 21 and have a positive beta value as well, indicating that the more effective tax-payers have the effect of increasing income tax revenue of the article 21 to come true.